2024
DOI: 10.1063/5.0190570
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the importance of four-phonon scattering in low-symmetry monolayer 1T′-ReS2 using machine learning potential

Xiao Yang,
Yong-Sen Chen,
Yu-Hao Zheng
et al.

Abstract: The importance of higher-order anharmonic effects on thermal transport has recently been demonstrated in highly symmetrical 2D materials with large acoustic–phonon (A–O) gap. However, the phonon scattering and the thermal transport properties in low-symmetry structures remain ambiguous. In this work, we employed moment tensor potential and Boltzmann transport equation to investigate phonon thermal transport properties of 1T′-ReS2 and 2H-WS2. We show that the mechanism of four-phonon scattering in 1T′-ReS2 is q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…On the other hand, the mentioned optimization of the used temperature grid could be performed possibly with the help of adaptive exchange techniques [35]. Depending on the final results obtained after considering the two previous mentioned improvements, additional studies related to the effects introduced by other physical microscopic phenomena could be carried out [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the mentioned optimization of the used temperature grid could be performed possibly with the help of adaptive exchange techniques [35]. Depending on the final results obtained after considering the two previous mentioned improvements, additional studies related to the effects introduced by other physical microscopic phenomena could be carried out [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…So far, great efforts have been denoted to study the manipulation method and microscopic mechanism of phonon thermal transport [10]. There has been found that the intrinsic phonon-phonon interaction [11,12], including third, fourth and higher order phonon scattering [13,14], plays a central role in the thermal transport properties of semiconductors and insulators. In addition, other ways to manipulate the κ through the size control, doping effect [15], defect, heterostructure and phonon interference [16] effect have also been widely studied.…”
Section: Introductionmentioning
confidence: 99%